Perovskite solar cell based on chalcogenide ligand material and preparation method thereof

By doping sulfur ligand materials in the perovskite before the perxonal antibody solution, the crystallization and lattice stress of the perovskite are adjusted, and the problem of stability in the day and night cycle mode is solved. Life and stability.

CN119364983AActive Publication Date: 2025-01-24SUZHOU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411315321.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-24
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The stability of perovskite solar cells in the day-night cycle mode has not been fully studied, especially in light and heat-induced lattice expansion and contraction, which affects the service life of the device.

Method used

By doping sulfur ligand materials in the precursor solution of perovskite, the use of sulfur elements and leading pica/pseudo -halogen volatile functional groups with sulfur ancestors and lead iodide, regulating the crystals and crystals of perovskite ore Stress stress, prepare a stable FAPBI3 film.

Benefits of technology

The lattice and contraction of the perovskite film in the day and night cycle mode is achieved, significantly improved the T80 life of the perovskite solar cell, and improved the stability and efficiency of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119364983A_ABST
    Figure CN119364983A_ABST
Patent Text Reader

Abstract

The invention discloses a chalcogenide ligand material-based perovskite solar cell and a preparation method thereof, which are characterized in that lattice stress which periodically changes in a day and night cycle working mode induces generation and accumulation of deep energy level defects of perovskite, and the ion migration behavior of the perovskite is aggravated, so that the performance degradation of a device is accelerated. A series of chalcogenide ligand materials are developed to eliminate lattice stress changes and stabilize perovskite lattices. Through double strategies of crystallization optimization and lattice anchoring, the pseudo-cubic phase FAPbI3 with higher symmetry and stability at room temperature is obtained, lattice expansion and contraction induced by light and heat are inhibited, and lattice stress change is eliminated. The perovskite solar cell prepared on the basis of the strategy has excellent photoelectric conversion efficiency (PCE) and stability, and the T80 service life is remarkably prolonged by 10 times in a day and night cycle working mode; meanwhile, the stability of the device based on a plurality of organic photovoltaic stability international peak committee (ISOS) tests is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photovoltaic materials, and specifically relates to the application of multifunctional sulfide ligand materials in perovskite solar cells, which can obtain high-efficiency and high-stability perovskite solar cells. Background Art

[0002] Over the past decade, research on the stability of perovskite solar cells in specific environments, such as high humidity (55-85% ambient humidity), high temperature (65-85°C), maximum power point tracking, and continuous light, has never stopped. Most of these studies are based on stability testing protocols (such as the International Summit on Organic Photovoltaic Stability Protocol (ISOS)) to evaluate the lifespan of perovskite solar cells, which usually only involve one specific environmental variable. However, in practical applications, perovskite solar cells operate in a day-night cycle mode, which often involves multiple external environmental changes, such as periodic light, temperature fluctuations, etc., making the degradation process of perovskites more complicated. To date, the stability of perovskite solar cells under the day-night cycle mode has rarely been studied.

[0003] At present, the most commonly used stability protocol (ISOS) for evaluating the life of perovskite solar cells draws on the standards of silicon solar cells. However, unlike single-crystal silicon, polycrystalline perovskite films have ion defects, and perovskite solar cells are prone to defect-induced "fatigue" behavior under the day-night cycle mode. Specifically, the device efficiency decays under illumination, and shallow energy level defects can "self-repair" the lattice in the dark environment to restore some efficiency. This "self-repair" behavior is not available in silicon solar cells. Therefore, the rigor of evaluating the life of perovskite solar cells according to the ISOS protocol is questionable. Studies have shown that under continuous illumination mode, the perovskite lattice expands and the lattice stress is gradually released; while under the day-night cycle mode, changes in light and temperature induce the "soft lattice" perovskite to expand and contract, generating periodic lattice stress. Most of the previous studies on the day-night cycle stability of perovskite solar cells stabilized the temperature at room temperature, ignoring the influence of temperature. Therefore, it is crucial to deeply study the impact of the superposition of light and heat on the device life under the day-night cycle mode.

[0004] In order to improve the service life of perovskite solar cells, researchers are keen to use functional molecular ligands to regulate the crystal orientation, phase composition and thermal expansion behavior of perovskites to stabilize the perovskite lattice. For example, in the preparation process of perovskite solar cells, organic ammonium salts, functional polymers, cross-linking agents, etc. are added to the perovskite precursor solution to prepare perovskite films, and the crystallization regulation mechanism or lattice anchoring effect of functional materials is used to improve the stability of perovskite solar cells. However, most of these strategies are aimed at solving the stability problems of perovskite solar cells under specific aging conditions, and there are few studies on improving the service life of perovskite solar cells under the day and night cycle working mode.

[0005] Therefore, it is urgent to explore an effective lattice stress regulation method that can not only achieve the preparation of room temperature stable FAPbI3 without affecting the perovskite components, but also effectively inhibit the light and heat induced lattice expansion and contraction, and reduce the influence of perovskite lattice strain on the stability of the device under the day and night cycle working mode, thereby preparing perovskite solar cells with high efficiency and excellent stability. Summary of the invention

[0006] The purpose of the present invention is to provide a perovskite solar cell and a preparation method thereof, by doping a chalcogenide ligand material with a perovskite precursor solution to prepare a room temperature stable FAPbI3 on ​​a conductive substrate, thereby inhibiting light and heat induced lattice expansion and contraction, and thereby obtaining a highly efficient and stable perovskite solar cell.

[0007] The chalcogenide ligand material designed by the present invention has not only aromatic groups (such as benzene rings) with high solubility, but also chalcogenide elements such as oxygen, sulfur, selenium, tellurium, and functional groups such as halogens / pseudohalogens. The chalcogenide elements have coordination bonds with lead iodide, and can react with lead iodide to form lead salts and anchor at the perovskite grain boundary to stabilize the perovskite lattice; the functional groups such as halogens / pseudohalogens are volatile, and can effectively regulate the growth kinetics of the perovskite film during thermal annealing to prepare room temperature stable FAPbI3. Due to the synergistic effect of chalcogenide elements and functional groups, perovskite has the effects of regulating crystallization, releasing lattice stress, and promoting transmission.

[0008] The present invention discloses a perovskite solar cell based on chalcogenide ligand materials, comprising a perovskite film layer doped with chalcogenide ligand materials. As common sense, the solar cell also comprises a conventional conductive substrate, an electron transport layer, a hole transport layer, and an anode.

[0009] The present invention discloses a method for preparing the above-mentioned perovskite solar cell based on chalcogenide ligand materials, comprising the following steps: preparing an electron transport layer on a conductive substrate; then spin coating a perovskite precursor solution doped with chalcogenide ligand materials on the electron transport layer, and then heat treating to obtain a perovskite film layer; then sequentially preparing a hole transport layer and an anode on the perovskite film to obtain a perovskite solar cell based on chalcogenide ligand materials, which has room temperature stability and low lattice stress.

[0010] The present invention also discloses a day-night cycle stability test method for perovskite solar cells, comprising the following steps: testing the power of the perovskite solar cell under sunlight, and then avoiding light; repeating the above test process to complete the day-night cycle stability test of the perovskite solar cell. Specifically, the perovskite solar cell is placed under 1 sun, illuminated for 12 hours (continuous tracking test at the maximum power point), and then restored in a dark environment for 12 hours (no bias); due to photoradiative heating, the device temperature fluctuates from ~55°C (light mode) to room temperature (dark mode).

[0011] The invention discloses a perovskite film based on a chalcogenide ligand material.

[0012] The present invention discloses a method for preparing the above-mentioned perovskite film based on chalcogenide ligand material, comprising the following steps: heat treating a perovskite precursor solution doped with chalcogenide ligand material to form a film, thereby obtaining a perovskite film based on chalcogenide ligand material.

[0013] The invention discloses the application of the above-mentioned perovskite film based on chalcogenide ligand material in the preparation of perovskite solar cells.

[0014] The invention discloses the application of a chalcogenide ligand material in preparing a perovskite solar cell or a perovskite film for a perovskite solar cell.

[0015] In the present invention, the heat treatment is performed at 140-160°C for 15-30 minutes; the doping concentration of the perovskite solution doped with the chalcogen ligand material is 0.2-2.0 mg mL -1 , preferably 0.5-1.0 mg mL -1 .

[0016] In the present invention, the perovskite precursor solution is a solution containing all perovskite precursors, or a solution containing part of the perovskite precursor and another solution containing the remaining part of the perovskite precursor; the former adopts a one-step spin coating method, preferably a one-step spin coating anti-solvent method, and the latter adopts a two-step spin coating method. This is a conventional method for preparing perovskite thin films. The creativity of the present invention lies in doping chalcogen ligand materials without changing the raw materials of the perovskite itself and its film-making method.

[0017] As an example, when the perovskite precursor solution is a solution containing part of the perovskite precursor (such as PbI2) and another solution containing the remaining part of the perovskite precursor (such as iodoformamide FAI), the PbI2 solution doped with the chalcogenide ligand material is spin-coated on the electron transport layer, and the FAI solution is spin-coated after annealing, and then heat-treated to obtain a perovskite film layer; or the PbI2 solution is spin-coated on the electron transport layer, and the FAI solution doped with the chalcogenide ligand material is spin-coated after annealing, and then heat-treated to obtain a perovskite film layer. The concentration of PbI2 is 600-750 mg / mL; in the FAI solution doped with the chalcogenide ligand material, the solvent is isopropanol, and the concentration of the FAI solution is 90-110 mg / mL. The doping concentration of the ligand material is 0.2-2.0 mg mL -1 , preferably 0.5-1.0 mg mL -1 .

[0018] In the present invention, during the heat treatment process, the ligand material and the precursor material react to generate volatile substances (hydrochloric acid, etc.) and lead salts, which effectively optimize the crystallization process of the perovskite, and the prepared room temperature stable pseudo cubic FAPbI3 avoids its phase change during the day and night cycle; at the same time, the lead salts anchored at the grain boundaries further inhibit the lattice expansion and contraction induced by light and temperature, thereby eliminating the lattice stress changes of the perovskite during the day and night cycle, and inhibiting the degradation of the perovskite. The present invention prepares an electron transport layer on a conductive substrate, and subsequently prepares a hole transport layer on the perovskite layer and an anode on the hole transport layer, which are all prior arts, and obtains an efficient and stable perovskite solar cell.

[0019] The preparation method of the perovskite layer disclosed in the present invention eliminates the periodic stress change of the perovskite lattice under the day-night cycle working mode, and enhances the actual working life of the perovskite solar cell. Therefore, under the day-night cycle mode, the perovskite solar cell prepared based on the chalcogenide ligand material has a T 80 The lifespan has been significantly increased by 10 times; at the same time, the stability of devices tested based on other ISOS protocols has also been greatly improved.

[0020] In the present invention, the chemical structural formula of the sulfide ligand material is as follows: ; Wherein, A is a chalcogen element, preferably a chalcogen element containing a lone pair of electrons, such as oxygen, sulfur, selenium, and tellurium; X is a volatile halogen or pseudo-halogen, such as iodine, bromine, amino, etc.; in the structural formula, the dotted line represents weak coordination, and the dot represents a free radical, which is a conventional representation method in the art and does not affect the understanding of those skilled in the art.

[0021] This invention reveals for the first time the unique degradation mechanism of perovskite solar cells under the day-night cycle mode, and emphasizes the necessity of stabilizing the lattice and eliminating lattice strain to enhance the actual working life of perovskite solar cells. In particular, a series of chalcogenide ligand materials have been developed to eliminate lattice stress changes and stabilize the perovskite lattice. The ligand material reacts with FAI during thermal annealing to form volatile substances, which optimizes the crystal growth dynamics of the perovskite and obtains a room temperature stable pseudo-cubic phase FAPbI3 with higher symmetry; in addition, the ligand material reacts with PbI2 to form lead salts and anchors at the grain boundaries, further suppressing the light- and heat-induced lattice expansion and contraction, eliminating lattice stress changes, and thus obtaining a highly efficient and stable perovskite solar cell.

[0022] Beneficial effects of the present invention: 1. The present invention grows a high-symmetry, low-strain perovskite lattice on a conductive substrate by doping a chalcogenide ligand material into a perovskite precursor solution, and based on this, prepares an efficient and stable perovskite solar cell.

[0023] 2. The present invention cleverly designs the chalcogen elements and volatile functional groups of the ligand materials, which regulate the perovskite crystallization and film morphology, greatly improving the lattice distortion of the perovskite film on the conductive substrate, thereby obtaining a stable perovskite film on the conductive substrate.

[0024] 3. The present invention discloses a day-night cycle stability test method. Under this day-night cycle mode, the service life of perovskite solar cells prepared based on sulfide ligand materials is significantly improved; at the same time, the stability of devices tested based on other ISOS protocols is also greatly improved.

[0025] 4. The preparation method of the present invention is simple, does not introduce additional interface layers or post-treatment processes, and the product has excellent performance and is suitable for industrial production.

[0026] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. The specific implementation of the present invention is given in detail by the following embodiments and their accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the NMR spectrum of phenylselenium chloride (Ph-Se-Cl).

[0028] Figure 2 The stress change diagram of the perovskite film calculated by curvature measurement under continuous illumination and day-night cycle working modes.

[0029] Figure 3XRD spectra of perovskite wet films (before annealing) based on different doping amounts of chalcogenide ligand materials and corresponding peak intensity ratio analysis.

[0030] Figure 4 HR-TEM image of perovskite film based on doped chalcogenide ligand material.

[0031] Figure 5 The lead salt powder of the reaction between the ligand material and PbI2 and the corresponding XRD pattern.

[0032] Figure 6 XRD diagram of temperature dependence of perovskite film before and after doping with chalcogenide ligand material.

[0033] Figure 7 In situ GIWAXS data of perovskite films before and after doping with chalcogenide ligand materials, as well as the changes in the unit cell volume and half-peak width parameters of the perovskite lattice during the in situ GIWAXS measurement.

[0034] Figure 8 The degradation mechanism of perovskite under the day-night cycle working mode, as well as the lattice parameters and spontaneous lattice stress of perovskite films at room temperature before and after doping with chalcogenide ligand materials.

[0035] Fig. 9 Cross-sectional SEM images of perovskite solar cells before and after aging under continuous illumination and day-night cycle operation modes before and after doping with chalcogenide ligand materials.

[0036] Fig.10 The activation energy of ion migration of perovskite solar cells before and after aging under continuous illumination and day-night cycle modes before and after doping with chalcogenide ligand materials.

[0037] Fig.11 The stability test of perovskite solar cells under continuous illumination and day-night cycle modes (RT~55℃) before and after doping with chalcogenide ligand materials.

[0038] Fig.12 This is a stability test of perovskite solar cells under day and night cycle mode (RT~85℃) before and after doping with chalcogenide ligand materials.

[0039] Fig.13 This is the 85℃ thermal stability test of perovskite solar cells before and after doping with chalcogenide ligand materials.

[0040] Fig.14 Thermal cycling stability (RT ~ 85 ° C) of perovskite solar cells before and after doping with chalcogenide ligand materials according to the ISOS-T-1 protocol.

[0041] Fig.15A statistical comparison of the stability of perovskite solar cells based on different perovskite components under continuous illumination and day-night cycle modes (RT~55°C) after doping with chalcogenide ligand materials (tested for 108 hours or 9 day-night cycles).

[0042] Fig.16 Current-voltage curve of perovskite solar cells based on chalcogenide ligand materials (effective area 0.062 cm 2 ). DETAILED DESCRIPTION

[0043] The present invention discloses for the first time the attenuation mechanism of perovskite solar cells under the day-night cycle working mode. Through in-situ crystal analysis and carrier dynamics research of perovskite, it is found that under the day-night cycle working mode, periodic illumination and temperature fluctuations cause the perovskite solar cell to synchronously undergo lattice expansion and contraction during operation, inducing cyclic changes in lattice stress. These periodically changing lattice stresses induce the generation and accumulation of deep energy level defects in perovskite, aggravating the ion migration behavior of perovskite, and accelerating the device performance attenuation compared with continuous illumination. The present invention develops a series of chalcogenide ligand materials to eliminate lattice stress changes and stabilize the perovskite lattice. Through the dual strategies of crystallization optimization and lattice anchoring, a room-temperature stable pseudo-cubic phase FAPbI3 with higher symmetry is obtained, which inhibits light- and heat-induced lattice expansion and contraction, and eliminates lattice stress changes. The perovskite solar cell prepared based on this strategy has excellent photoelectric conversion efficiency (PCE) and stability, and maintains stable performance under the day-night cycle working mode. T 80 The lifespan has been significantly increased by 10 times; at the same time, the device stability based on various International Organic Photovoltaic Stability Summit Protocols (ISOS) tests has been greatly improved.

[0044] A perovskite solar cell based on a chalcogenide ligand material disclosed in the present invention comprises a perovskite layer, and a raw material for preparing the perovskite layer comprises a chalcogenide ligand material. Preferably, the raw material for preparing the perovskite layer comprises a perovskite precursor solution doped with a chalcogenide ligand material.

[0045] Preferably, the chemical structural formula of the sulfide ligand material is as follows: ; Wherein, X is a halogen or pseudo-halogen substituent; A is a chalcogen element containing a lone pair of electrons.

[0046] The present invention prepares an electron transport layer on a conductive substrate; then spin-coats a perovskite precursor solution doped with a chalcogenide ligand material on the electron transport layer, and then performs a heat treatment to obtain a perovskite film layer; then sequentially prepares a hole transport layer and an anode on the perovskite film to obtain a perovskite solar cell based on a chalcogenide ligand material, which has room temperature stability and low lattice stress. Preferably, the heat treatment is performed at 140 to 160°C for 10 to 20 minutes.

[0047] In the present invention, the perovskite precursor solution is a solution containing all perovskite precursors, or a solution containing part of the perovskite precursor and another solution containing the remaining part of the perovskite precursor; the former adopts a one-step spin coating method, preferably a one-step spin coating anti-solvent method, and the latter adopts a two-step spin coating method. This is a conventional method for preparing perovskite thin films. The creativity of the present invention lies in doping chalcogen ligand materials without changing the raw materials of the perovskite itself and its film-making method.

[0048] Taking two groups of perovskite precursor solutions as an example, in the method for preparing an efficient and stable perovskite solar cell based on chalcogenide ligand materials of the present invention, detailed information of each step is as follows: (1) First, prepare a PbI2 DMF solution doped with a chalcogenide ligand material and a FAI isopropanol solution; or prepare a PbI2 DMF solution and a FAI isopropanol solution doped with a chalcogenide ligand material; (2) Spin-coat a layer of SnO2 on the clean FTO with a thickness of 10 to 20 nm; (3) Spin coating the prepared PbI2 solution on SnO2, annealing to obtain a lead iodide film, and then spin coating the FAI solution, annealing to obtain a perovskite film with a thickness of 600 to 700 nm; or spin coating the PbI2 solution on the SnO2 layer, annealing, and then spin coating the FAI solution doped with a chalcogenide ligand material, and then heat treating to obtain a perovskite film layer; (4) Spin-coating Spiro-OMeTAD as a hole transport layer with a thickness of 80 to 100 nm; (5) The electrode is a gold electrode, which is deposited by a vacuum evaporator and has a thickness of 100 nm.

[0049] The embodiments of the present invention disclose three chalcogenide ligand materials with chemical structures. As examples, the present invention discloses a preparation method of a representative chalcogenide ligand material.

[0050] The preparation method of phenylselenium chloride (Ph-Se-Cl), a chalcogenide ligand material, comprises the following steps: adding sulfonyl chloride dropwise into a diphenyl diselenide solution in an inert gas, then stirring the reaction at room temperature, and finally concentrating the obtained mixture under reduced pressure to obtain an orange solid, which can be used without further purification.

[0051] The preparation method of sulfide ligand material phenylsulfur chloride (Ph-S-Cl) comprises the following steps: adding sulfonyl chloride to diphenyl disulfide solution in an inert gas, then reacting at room temperature, and finally concentrating the obtained mixture under reduced pressure to obtain a dark red oil, which can be used without further purification.

[0052] The preparation method of sulfide ligand material phenyltellurium chloride (Ph-Te-Cl) comprises the following steps: adding sulfonyl chloride to diphenyl ditelluride ether solution in an inert gas, then reacting at room temperature, and finally concentrating the obtained mixture under reduced pressure to obtain a black solid, which can be used without further purification.

[0053] The present invention will be described in detail below in conjunction with the examples. The raw materials involved are all existing products, and the specific preparation methods and performance test operations are conventional techniques; FTO is routinely cleaned before use and used as a conductive substrate.

[0054] The photoelectric performance of the device was measured by simulating 1 sun illumination (100 mW cm) with a Newport xenon lamp AM 1.5G. -2 ) was measured using a source meter (Keithley 2400) and a standard silicon cell with a KG-5 filter was used for light intensity calibration. The steady-state power conversion efficiency was calculated by measuring the stable photocurrent density at a constant bias voltage (Vmax point), where the effective area of ​​the device was corrected with a precise aperture (0.062 and 1.004 cm 2 ). Embodiment 1

[0055] A method for preparing phenylselenium chloride (Ph-Se-Cl), a chalcogenide ligand material, comprises the following steps: dripping a solution of diphenyl diselenide (1.56 mL, 5 mmol) in anhydrous dichloromethane (20 mL) into a 50 mL round-bottom flask at 0°C, the flask is filled with argon, and then dripping sulfonyl chloride (0.67 mL, 5 mmol) after stirring; then further stirring at room temperature for 1 h; finally, concentrating the obtained mixture under reduced pressure to obtain an orange solid, which can be used without further purification.

[0056] Other chalcogenide ligand materials, such as phenylsulfur chloride (Ph-S-Cl) and phenyltellurium chloride (Ph-Te-Cl), can be prepared by referring to the above method.

[0057] Figure 1 Phenylselenium chloride (Ph-Se-Cl) 1 HNMR spectra and 13 C NMR spectrum. 1H NMR (300 MHz, CDCl3): δ = 7.82-7.79 (m, 2H), 7.43-7.41 (m, 3H); 13 C NMR (151 MHz, CDCl3): δ = 134.4, 131.7, 130.6, 129.6.

[0058] Unless otherwise specified, the following experiments used phenylselenium chloride (Ph-Se-Cl) as the chalcogenide ligand material. Embodiment 2

[0059] A method for preparing a perovskite film and a film stress test thereof, comprising the following steps: (1) Spin-coat a layer of SnO2 on the clean FTO using a tin dioxide dispersion (7.5% hydrocolloid) at a speed of 3000 rpm and anneal at 150 °C for 30 min to a thickness of 15 nm. (2) Prepare the PbI2 solution (PbI2 concentration is 692 mg mL -1 ) was spin-coated on SnO2 and annealed to obtain a doped lead iodide film at a rotation speed of 1500 rpm and annealed at 70°C for 1 min; then, FAI isopropanol solution (the concentration of FAI was 90 mg mL -1 ), and then annealed at 150 °C for 15 min to obtain an undoped perovskite film with a thickness of 650 nm.

[0060] (3) The perovskite film was placed under continuous illumination or day-night cycle mode for stress evolution tracking test. Under continuous illumination mode, the device was placed under 1 sun and the temperature control table was set at 25°C; under day-night cycle mode, the device was placed under 1 sun, and after 30 minutes of illumination, it was restored in a dark environment for about 20 minutes (no bias). Due to photoradiative heating, the device temperature fluctuated from ~55°C (illumination) to room temperature (dark state).

[0061] The prepared films were used for stress tests, such as Figure 2 As shown in the figure, the curvature of the perovskite film and the substrate was measured by the Linkam heating stage, and the stress change of the perovskite film under continuous illumination and day-night cycle mode was calculated based on the change in curvature. Stress measurement shows that in the continuous illumination mode, with the increase of illumination time and the temperature fixed at room temperature, the stress of the perovskite film is released from ~84 MPa to ~68 MPa within 4 hours; in the day-night cycle mode, the stress of the perovskite film changes synchronously with the changes in illumination and temperature (the change value is ~40 MPa), indicating that in the day-night cycle mode, the periodic change of the stress of the perovskite film accelerates the attenuation of the performance of the perovskite solar cell. Embodiment 3

[0062] A method for preparing a perovskite film doped with a chalcogenide ligand material comprises the following steps: (1) First, prepare a PbI2 DMF solution (PbI2 concentration is 692 mg mL -1 ) and materials doped with different amounts of chalcogenide ligands (0~2 mg mL -1 ) in isopropanol solution of FAI (concentration 90 mg mL -1 ); (2) The perovskite layer was prepared by a two-step method. The prepared PbI2 solution was spin-coated on a clean FTO substrate and annealed to obtain a PbI2 film at a rotation speed of 1500 rpm and annealed at 70°C for 1 min. Then, FAI isopropanol solution was spin-coated on the dried PbI2 film. The prepared perovskite film was not subjected to thermal annealing. The unannealed perovskite film was subjected to XRD test. Figure 3 As shown, with the increase of Ph-Se-Cl doping concentration, the peak intensity ratio of α-FAPbI3 / PbI2 and intermediate phase / PbI2 increases, indicating that Ph-Se-Cl promotes the phase transformation of PbI2 to perovskite α phase, optimizes the crystal orientation of perovskite, and helps to improve the quality of perovskite film. Embodiment 4

[0063] A method for preparing a perovskite film doped with a chalcogenide ligand material comprises the following steps: (1) First, prepare a PbI2 DMF solution (PbI2 concentration is 692 mg mL -1 ) and chalcogenide-doped materials (0.5 mg mL -1 ) in isopropanol solution of FAI (concentration 90 mg mL -1 ); (2) The perovskite layer was prepared by a two-step method. The prepared PbI2 solution was spin-coated on a clean FTO substrate and annealed to obtain a PbI2 film at a speed of 1500 rpm and annealed at 70°C for 1 min. Then, FAI isopropanol solution was spin-coated on the dried PbI2 film. (3) Then annealing was performed at 150 °C for 15 min to obtain the doped perovskite film.

[0064] The prepared film was used for HR-TEM test, such as Figure 4As shown, according to the FFT analysis of the HR-TEM image of the perovskite film doped with Ph-Se-Cl, it can be obtained that the lattice spacing of region 1 and region 2 are 3.2 and 7.4 Å, respectively, which are attributed to the (002) crystal plane of α-FAPbI3 and the new substance, respectively, indicating that Ph-Se-Cl can react with PbI2 to form lead salts.

[0065] A method for preparing a new substance by reacting Ph-Se-Cl with PbI2 comprises the following steps: (1) First, 1.5 M PbI2 and 1.5 M Ph-Se-Cl powders were dissolved in 1 mL DMF and stirred at 50 °C overnight; (2) The solution was then filtered and transferred into a 4 mL brown bottle, which was then sealed with 2 mL of tetrahydrofuran solution. (3) Yellow powder precipitates as tetrahydrofuran vapor slowly diffuses.

[0066] In order to further explore the composition of the light yellow powder, the powder was subjected to XRD test, such as Figure 5 As shown, the powder has a diffraction peak near 7.03°, indicating the formation of lead salt. This peak is also consistent with the lattice spacing tested by HR-TEM. Combined with Example 3, Ph-Se-Cl has two functions in the perovskite film: first, Ph-Se-Cl reacts with FAI during thermal annealing to form volatile substances, optimizing the crystal growth dynamics of perovskite; secondly, Ph-Se-Cl reacts with PbI2 to form lead salts and anchors them at the grain boundaries, improving the lattice stability of perovskite. Embodiment 5

[0067] A method for preparing a perovskite film doped with a chalcogenide ligand material comprises the following steps: (1) First, prepare the sulfide ligand-doped material (0.5 mg mL -1 ) in isopropanol solution of FAI (concentration 90 mg / mL -1 ), undoped FAI isopropanol solution (concentration 90 mg mL -1 ) and PbI2 DMF solution (the concentration of PbI2 was 692 mgmL -1 ); (2) The perovskite layer was prepared by a two-step method. The prepared PbI2 solution was spin-coated on a clean FTO substrate and annealed at 1500 rpm and 70°C for 1 min to obtain a PbI2 film. Then, an undoped or doped FAI isopropanol solution with a chalcogenide ligand material was spin-coated on the dried PbI2 film and then annealed at 150°C for 15 min to obtain a perovskite film.

[0068] (3) XRD test of perovskite films during thermal annealing cooling (150℃, 125℃, 100℃, 75℃, 50℃, 25℃) like Figure 6 As shown in Figure 2, it is the XRD spectrum of the above perovskite film. It can be seen from the figure that the peak of the undoped perovskite film around 28° is symmetrical at 150°C. When the temperature drops from 150°C to 25°C, the peak shape of the (004) / (220) characteristic diffraction peak becomes asymmetrical, and the peak of the (002) / (110) characteristic diffraction peak shifts to a higher angle, indicating that the lattice volume shrinks during the cooling process and the lattice is distorted. However, the doped perovskite film always maintains a highly symmetrical pseudo-cubic phase during the thermal annealing cooling process, which inhibits the temperature-induced lattice phase transition. Embodiment 6

[0069] A method for preparing a perovskite film doped with a chalcogenide ligand material comprises the following steps: (1) First, prepare the sulfide ligand-doped material (0.5 mg mL -1 ) in isopropanol solution of FAI (concentration 90 mg / mL -1 ), undoped FAI isopropanol solution (concentration 90 mg mL -1 ) and PbI2 DMF solution (the concentration of PbI2 was 692 mgmL -1 ); (2) The perovskite layer was prepared by a two-step method. The prepared PbI2 solution was spin-coated on a clean silicon substrate and annealed at 1500 rpm and 70°C for 1 min to obtain a PbI2 film. Then, an undoped or doped FAI isopropanol solution with a chalcogenide ligand material was spin-coated on the dried PbI2 film and then annealed at 150°C for 15 min to obtain a perovskite film.

[0070] (3) An in-situ GIWAXS test was performed on the perovskite film (simulating a day-night cycle mode). The specific scheme is as follows: the cycle starts from the dark state and room temperature, then the light source is turned on (the light source is a cold light source), and the substrate temperature is raised to ~55°C within 5 minutes. The perovskite film is monitored for 90 minutes under the combined effects of light and temperature; then the light source is turned off and the substrate temperature control is stopped, and it is cooled to room temperature within 30 minutes. This is one cycle, and 2 cycles are tested.

[0071] like Figure 7 As shown in Figure 2, with the increase of monitoring time, the (002) and (110) diffraction peaks of the undoped perovskite film shift to smaller q The value shifts, indicating that the perovskite lattice expands, and then q The value tends to be stable; when the sample cools to room temperature, qThe value returns to the initial state, and the perovskite lattice shrinks. The unit cell volume and half-peak width of the perovskite were calculated based on the test results of in-situ GIWAXS. It was found that the unit cell volume of the perovskite changed greatly (~0.48%) under the day-night cycle mode, and the half-peak width of the (002) & (110) characteristic peaks increased and decreased synchronously with the changes in light and temperature, indicating that the perovskite lattice will expand and shrink under the day-night cycle mode. However, the (002) & (110) diffraction peaks of the doped perovskite film hardly shifted, and the calculated perovskite unit cell volume and peak width changes were also very small (~0.04%), indicating that Ph-Se-Cl effectively suppressed the volume change of the lattice and stabilized the perovskite lattice.

[0072] Table 1 Normalized unit cell parameters and calculated spontaneous strain of perovskite films

[0073] By analyzing the crystal structure of perovskite at room temperature, such as Figure 8 As shown in Table 1, it is found that the perovskite doped with chalcogenide ligand material presents a pseudo-cubic phase at room temperature, while the undoped perovskite presents a γ phase at room temperature. The lattice stress generated by the perovskite during the phase transition was then calculated, and it was found that the spontaneous lattice stress (e tet and e orth value) decreases, indicating that Ph-Se-Cl effectively releases the spontaneous lattice strain and helps to suppress the periodic lattice stress changes caused by the perovskite phase transition under the day-night cycle mode. Embodiment 7

[0074] A method for preparing a perovskite solar cell comprises the following steps: (1) First, prepare the sulfide ligand-doped material (0.5 mg mL -1 ) in isopropanol solution of FAI (concentration 90 mg / mL -1 ), undoped FAI isopropanol solution (concentration 90 mg mL -1 ) and PbI2 DMF solution (the concentration of PbI2 was 692 mgmL -1 ); (2) On a clean 1.5×1.5 cm 2 A layer of SnO2 was spin-coated on the FTO conductive substrate using a tin dioxide dispersion (7.5% aqueous colloid) at a spin-coating speed of 3000 rpm and annealed at 150 °C for 30 min to a thickness of 15 nm. (3) The perovskite layer was prepared by a two-step method. The prepared PbI2 solution was spin-coated on SnO2 and annealed to obtain a lead iodide film at a rotation speed of 1500 rpm and annealed at 70°C for 1 min. Then, an undoped or doped FAI isopropanol solution of a chalcogenide ligand material was spin-coated on the dried PbI2 film. The perovskite film was then annealed on a hot plate at 150°C for 15 min to obtain a 650 nm thick perovskite film. (4) Spiro-OMeTAD was prepared as a hole transport layer on the perovskite film. The solvent was chlorobenzene with a concentration of 72.3 mg mL -1 , the spin coating speed was 3000 rpm and the thickness was 90 nm; (5) The film was placed in a vacuum coating machine to evaporate a gold electrode with a thickness of 100 nm, and the final effective area was 0.062 cm 2 Doped flexible perovskite solar cells; (6) The above-mentioned devices were subjected to aging tests in continuous illumination working mode or day-night cycle working mode. In continuous illumination working mode, the device was placed under 1 sun and tracked at the maximum power point. Due to photoradiative heating, the device temperature gradually increased from room temperature to ~55°C. In day-night cycle mode, the device was placed under 1 sun and illuminated for 12 hours (tracking test at maximum power point) and then recovered in a dark environment for 12 hours (no bias). Due to photoradiative heating, the device temperature fluctuated from ~55°C (illumination) to room temperature (dark state). The perovskite film was aged for 156 h and 13 cycles in continuous illumination and day-night cycle working modes, respectively (same illumination time).

[0075] The aged device was subjected to cross-sectional SEM test, such as Fig. 9 As shown in the figure, the undoped perovskite film after aging in both working modes has holes and interface cracks, indicating that the attenuation of device performance is related to the plastic deformation induced by film strain; at the same time, the film deforms and degrades more seriously in the day-night cycle mode, indicating that the day-night cycle mode will accelerate the degradation of perovskite. However, the perovskite film doped with chalcogenide ligand materials has no holes and cracks after aging in both working modes, and the morphology is consistent and dense, indicating that Ph-Se-Cl can effectively release the lattice stress of the perovskite film, inhibit the change of the perovskite lattice volume, and significantly improve the stability of the perovskite film, especially the day-night cycle stability. Embodiment 8

[0076] A method for preparing a perovskite solar cell comprises the following steps: (1) First, prepare the sulfide ligand-doped material (0.5 mg mL -1 ) in isopropanol solution of FAI (concentration 90 mg / mL-1 ), undoped FAI isopropanol solution (concentration 90 mg mL -1 ) and PbI2 DMF solution (the concentration of PbI2 was 692 mgmL -1 ); (2) On a clean 1.5×1.5 cm 2 A layer of SnO2 was spin-coated on the FTO conductive substrate using a tin dioxide dispersion (7.5% aqueous colloid) at a spin-coating speed of 3000 rpm and annealed at 150 °C for 30 min to a thickness of 15 nm. (3) The perovskite layer was prepared by a two-step method. The prepared PbI2 solution was spin-coated on SnO2 and annealed to obtain a lead iodide film at a rotation speed of 1500 rpm and annealed at 70°C for 1 min. Then, an undoped or doped FAI isopropanol solution of a chalcogenide ligand material was spin-coated on the dried PbI2 film. The film was then annealed on a hot plate at 150°C for 15 min to obtain a perovskite film with a thickness of 650 nm. (4) Spiro-OMeTAD was prepared as a hole transport layer on the perovskite film. The solvent was chlorobenzene with a concentration of 72.3 mg mL -1 , the spin coating speed was 3000 rpm and the thickness was 90 nm; (5) The film was placed in a vacuum coating machine to evaporate a gold electrode with a thickness of 100 nm, and the final effective area was 0.062 cm 2 Doped flexible perovskite solar cells; (6) The above-mentioned devices were subjected to aging tests in a continuous illumination working mode or a day-night cycle working mode. In the continuous illumination working mode, the device was placed under one sun and tracked at the maximum power point. Due to photoradiation heating, the device temperature gradually increased from room temperature to ~55°C. In the day-night cycle mode, the device was placed under one sun, illuminated for 12 hours (tracking test at the maximum power point) and then restored in a dark environment for 12 hours (no bias). Due to photoradiation heating, the device temperature fluctuated from ~55°C (illumination) to room temperature (dark state).

[0077] The ion migration activation energy ( E a ) test, such as Fig.10 As shown, the initial E a is ~0.25 eV after aging for 84 hours under continuous light. E a After further aging for 168 hours, it drops to ~0.19 eV. E aIt decreases to ~0.18 eV, indicating that with the increase of aging time, E a The downward trend of E a After 7 cycles of aging (84 hours of light exposure), E a After further aging for 14 cycles (168 h of illumination), E a Down to ~0.13 eV. In the day-night cycle mode E a The rapid decrease in indicates that the periodic changes in the perovskite lattice stress accelerate the ion migration of perovskite solar cells, resulting in faster performance decay; After doping with chalcogenide ligand materials, the initial E a Increased from ~0.25 eV to ~0.38 eV; compared to undoped perovskite solar cells during aging E a The perovskite solar cells doped with chalcogenide ligand materials undergo aging under continuous illumination and day-night cycle modes. E a The above results show that the chalcogenide ligand material can effectively release the lattice stress of the perovskite film, inhibit the volume change of the perovskite lattice, thereby inhibiting the ion migration behavior of the perovskite solar cell and significantly improving the stability of the perovskite solar cell. Embodiment 9

[0078] A method for preparing a perovskite solar cell comprises the following steps: (1) First, prepare the sulfide ligand-doped material (0.5 mg mL -1 ) in isopropanol solution of FAI (concentration 90 mg / mL -1 ), undoped FAI isopropanol solution (concentration 90 mg mL -1 ) and PbI2 DMF solution (the concentration of PbI2 was 692 mgmL -1 ); (2) On a clean 1.5×1.5 cm 2 A layer of SnO2 was spin-coated on the FTO conductive substrate using a tin dioxide dispersion (7.5% aqueous colloid) at a spin-coating speed of 3000 rpm and annealed at 150 °C for 30 min to a thickness of 15 nm. (3) The perovskite layer was prepared by a two-step method. The prepared PbI2 solution was spin-coated on SnO2 and annealed to obtain a lead iodide film at a rotation speed of 1500 rpm and annealed at 70°C for 1 min. Then, an undoped or doped FAI isopropanol solution of a chalcogenide ligand material was spin-coated on the dried PbI2 film. The film was then annealed on a hot plate at 150°C for 15 min to obtain a perovskite film with a thickness of 650 nm. (4) Spiro-OMeTAD was prepared as a hole transport layer on the perovskite film. The solvent was chlorobenzene with a concentration of 72.3 mg mL -1 , the spin coating speed was 3000 rpm and the thickness was 90 nm; (5) The film was placed in a vacuum coating machine to evaporate a gold electrode with a thickness of 100 nm, and the final effective area was 0.062 cm 2 Doped flexible perovskite solar cells; (6) The above-mentioned devices were subjected to aging tests in a continuous illumination working mode or a day-night cycle working mode. In the continuous illumination working mode, the device was placed under one sun and tracked at the maximum power point. Due to photoradiation heating, the device temperature gradually increased from room temperature to ~55°C. In the day-night cycle mode, the device was placed under one sun, illuminated for 12 hours (tracking test at the maximum power point) and then restored in a dark environment for 12 hours (no bias). Due to photoradiation heating, the device temperature fluctuated from ~55°C (illumination) to room temperature (dark state).

[0079] like Fig.11 As shown in the results, the perovskite solar cell doped with chalcogenide ligands still retains more than 90% of its initial efficiency (PCE) after 1000 hours of operation in continuous illumination mode, while the undoped perovskite solar cell only retains ~44% of its initial PCE after 375 hours of operation; more importantly, the stability of the perovskite solar cell doped with chalcogenide ligands is also significantly improved in the day-night cycle mode: after 43 cycles of aging, the perovskite solar cell doped with chalcogenide ligands still retains more than 80% of its initial PCE, while the undoped perovskite solar cell only retains ~39% of its initial PCE after 13 cycles of aging. This is one of the best stabilities among perovskite solar cells based on Spiro-OMeTAD HTL. Embodiment 10

[0080] A method for preparing a perovskite solar cell comprises the following steps: (1) First, prepare the sulfide ligand-doped material (0.5 mg mL -1 ) in isopropanol solution of FAI (concentration 90 mg / mL -1), undoped FAI isopropanol solution (concentration 90 mg mL -1 ) and PbI2 DMF solution (the concentration of PbI2 was 692 mgmL -1 ); (2) On a clean 1.5×1.5 cm 2 A layer of SnO2 was spin-coated on the FTO conductive substrate using a tin dioxide dispersion (7.5% aqueous colloid) at a spin-coating speed of 3000 rpm and annealed at 150 °C for 30 min to a thickness of 15 nm. (3) The perovskite layer was prepared by a two-step method. The prepared PbI2 solution was spin-coated on SnO2 and annealed to obtain a lead iodide film at a rotation speed of 1500 rpm and annealed at 70°C for 1 min. Then, an undoped or doped FAI isopropanol solution of a chalcogenide ligand material was spin-coated on the dried PbI2 film. The film was then annealed on a hot plate at 150°C for 15 min to obtain a perovskite film with a thickness of 650 nm. (4) Prepare BDT-DPA-F as a hole transport layer on the perovskite film. The solvent is chlorobenzene with a concentration of 10.0 mg / mL -1 , the spin coating speed was 3000 rpm and the thickness was 40 nm; (5) The film was placed in a vacuum coating machine to evaporate a gold electrode with a thickness of 100 nm, and the final effective area was 0.062 cm 2 Doped flexible perovskite solar cells; (6) The above devices were subjected to aging tests in different modes: the thermal stability and thermal cycling stability of perovskite solar cells were tested according to the ISOS-D-2 and ISOS-T-1 stability protocols; for the stability in the day-night cycle working mode, the device was placed under 1 sun for 12 hours (tracking test at maximum power point) and then recovered in a dark environment for 12 hours (no bias), and the device temperature fluctuated from ~85°C (light) to room temperature (dark state).

[0081] like Fig.12 As shown in Figure 2, the perovskite solar cell doped with chalcogenide ligand materials retained more than 96% of its initial PCE after running for 25 day-night cycles, while the undoped perovskite solar cell only retained ~27% of its initial PCE; Fig.13 As shown in Figure 2, the PCE of the perovskite solar cell doped with chalcogenide ligand material decays very little (~5%) after thermal aging for 1000 h at 85°C, while the PCE of the undoped perovskite solar cell decays by ~20% under the same conditions; Fig.14As shown in the figure, in the thermal cycle aging measurement, the efficiency of the perovskite solar cell doped with chalcogenide ligand material at 85°C and at room temperature after aging for 25 cycles retained more than 96% of its initial PCE, while the undoped perovskite solar cell only retained ~80% and ~84% of its initial PCE. These stability evaluation results of perovskite solar cells conducted under different stability test conditions indicate that the crystallization optimization and lattice anchoring strategy of chalcogenide ligand materials can significantly improve the stability of perovskite solar cells under various aging conditions, greatly promoting the commercial development of perovskite solar cells. Embodiment 11

[0082] A method for preparing a perovskite solar cell comprises the following steps: (1) First, prepare the sulfide ligand-doped material (0.5 mg mL -1 ) in isopropanol solution of FAI (concentration 90 mg / mL -1 ), undoped FAI isopropanol solution (concentration 90 mg mL -1 ) and PbI2 DMF solution (the concentration of PbI2 was 692 mgmL -1 ); (2) On a clean 1.5×1.5 cm 2 A layer of SnO2 was spin-coated on the FTO conductive substrate using a tin dioxide dispersion (7.5% aqueous colloid) at a spin-coating speed of 3000 rpm and annealed at 150 °C for 30 min to a thickness of 15 nm. (3) The perovskite layer was prepared by a two-step method. The prepared PbI2 solution was spin-coated on SnO2 and annealed to obtain a lead iodide film at a rotation speed of 1500 rpm and annealed at 70°C for 1 min. Then, an undoped or doped FAI isopropanol solution of a chalcogenide ligand material was spin-coated on the dried PbI2 film. The film was then annealed on a hot plate at 150°C for 15 min to obtain a perovskite film with a thickness of 650 nm. (4) Spiro-OMeTAD was prepared as a hole transport layer on the perovskite film. The solvent was chlorobenzene with a concentration of 72.3 mg mL -1 , the spin coating speed was 3000 rpm and the thickness was 90 nm; (5) The film was placed in a vacuum coating machine to evaporate a gold electrode with a thickness of 100 nm, and the final effective area was 0.062 cm 2 Doped flexible perovskite solar cells.

[0083] A method for preparing a perovskite solar cell comprises the following steps: (1) First, prepare the sulfide ligand-doped material (0.5 mg mL-1 ) isopropanol solutions of FAI, MAI, and MACl (FAI 90 mg, MAI 6.39 mg, and MACl 9 mg dissolved in 1 mL IPA solution), undoped isopropanol solutions of FAI, MAI, and MACl (FAI 90 mg, MAI 6.39 mg, and MACl 9 mg dissolved in 1 mL IPA solution), and PbI2 DMF solutions (the concentration of PbI2 was 692 mg mL -1 ); (2) On a clean 1.5×1.5 cm 2 A layer of SnO2 was spin-coated on the FTO conductive substrate using a tin dioxide dispersion (7.5% aqueous colloid) at a spin-coating speed of 3000 rpm and annealed at 150 °C for 30 min to a thickness of 15 nm. (3) The perovskite layer was prepared by a two-step method. The prepared PbI2 solution was spin-coated on SnO2 and annealed to obtain a lead iodide film at a rotation speed of 1500 rpm and annealed at 70°C for 1 min. Then, undoped or doped chalcogenide ligand material FAI, MAI and MACl isopropanol solutions were spin-coated on the dried PbI2 film. The perovskite film was then annealed on a hot plate at 150°C for 15 min to obtain a perovskite film with a thickness of 550 nm. (4) Spiro-OMeTAD was prepared as a hole transport layer on the perovskite film. The solvent was chlorobenzene with a concentration of 72.3 mg mL -1 , the spin coating speed was 3000 rpm and the thickness was 90 nm; (5) The film was placed in a vacuum coating machine to evaporate a gold electrode with a thickness of 100 nm, and the final effective area was 0.062 cm 2 Doped flexible perovskite solar cells.

[0084] A method for preparing a perovskite solar cell comprises the following steps: (1) First, prepare undoped and doped chalcogenide ligand materials (0.5 mg mL -1 ) perovskite precursor solution, 1.37 M PbI2, 0.20 M PbBr2, 1.29 M FAI, 0.20 M MABr and 0.40 M MACl were dissolved in 1 mL DMF and DMSO mixed solution (volume ratio DMF:DMSO = 4:1), and then 44 μL of CsI DMSO solution (1.5 M) was added; (2) On a clean 1.5×1.5 cm 2A layer of SnO2 was spin-coated on the FTO conductive substrate using a tin dioxide dispersion (7.5% aqueous colloid) at a spin-coating speed of 3000 rpm and annealed at 150 °C for 30 min to a thickness of 15 nm. (3) The perovskite layer was prepared by a one-step method. The prepared perovskite precursor solution was applied to SnO2, first spin-coated at 1000 rpm for 10 s and then spin-coated at 5000 rpm for 30 s. After 15 s, 120 μL of chlorobenzene was spin-coated onto the film as an anti-solvent. The perovskite film was then transferred to an air environment (humidity of about 20%) and thermally annealed at 105 °C for 30 min. The thickness was 550 nm. (4) Spiro-OMeTAD was prepared as a hole transport layer on the perovskite film. The solvent was chlorobenzene with a concentration of 72.3 mg mL -1 , the spin coating speed was 3000 rpm and the thickness was 90 nm; (5) The film was placed in a vacuum coating machine to evaporate a gold electrode with a thickness of 100 nm, and the final effective area was 0.062 cm 2 Doped flexible perovskite solar cells.

[0085] The above devices were subjected to aging tests under continuous illumination working mode or day-night cycle working mode. Under continuous illumination working mode, the device was placed under 1 sun and tracked at the maximum power point. Due to photoradiation heating, the device temperature gradually increased from room temperature to ~55°C. Under day-night cycle mode, the device was placed under 1 sun, illuminated for 12 hours (tracking test at maximum power point) and then recovered in a dark environment for 12 hours (no bias). Due to photoradiation heating, the device temperature fluctuated from ~55°C (illumination) to room temperature (dark state).

[0086] The three different perovskite solar cells were aged for 108 h or 9 day-night cycles (same illumination time) under continuous illumination and day-night cycle operation mode. Fig.15 As shown, after doping with chalcogenide ligand materials, based on FAPbI3, FA 0.92 MA 0.08 PbI3 and Cs-based 0.05 FA 0.7 MA 0.25 PbI 2.6 Br 0.4 The stability of active layer component perovskite solar cells is enhanced in both working modes (PCE retention rate is high), which shows that the dual strategy of crystallization regulation and lattice anchoring based on chalcogenide ligand materials effectively slows down the perovskite degradation caused by lattice stress and has universal applicability, laying a solid foundation for the commercial development of perovskite solar cells. Embodiment 12

[0087] A high-efficiency perovskite solar cell (effective area 0.062 cm 2 ), comprising the following steps: (1) First, prepare the sulfide ligand-doped material (0.5 mg mL -1 ) in isopropanol solution of FAI (concentration 90 mg / mL -1 ), undoped FAI isopropanol solution (concentration 90 mg mL -1 ) and PbI2 DMF solution (the concentration of PbI2 was 692 mgmL -1 ); (2) On a clean 1.5×1.5 cm 2 A layer of SnO2 was spin-coated on the FTO conductive substrate using a tin dioxide dispersion (7.5% aqueous colloid) at a spin-coating speed of 3000 rpm and annealed at 150 °C for 30 min to a thickness of 15 nm. (3) The perovskite layer was prepared by a two-step method. The prepared PbI2 solution was spin-coated on SnO2 and annealed to obtain a lead iodide film at a rotation speed of 1500 rpm and annealed at 70°C for 1 min. Then, an undoped or doped FAI isopropanol solution of a chalcogenide ligand material was spin-coated on the dried PbI2 film. The film was then annealed on a hot plate at 150°C for 15 min to obtain a perovskite film with a thickness of 650 nm. (4) Spiro-OMeTAD was prepared as a hole transport layer on the perovskite film. The solvent was chlorobenzene with a concentration of 72.3 mg mL -1 , the spin coating speed was 3000 rpm and the thickness was 90 nm; (5) The film was placed in a vacuum coating machine to evaporate a gold electrode with a thickness of 100 nm, and the final effective area was 0.062 cm 2 Doped flexible perovskite solar cells.

[0088] The performance of the above perovskite solar cells is shown in Fig.16 (Current-voltage curve of perovskite solar cell) and Table 2, light intensity is AM1.5G 100 mW cm -2 .

[0089] Table 2 Photovoltaic parameters of perovskite solar cells

[0090] Different from the currently developed perovskite additive strategy, the present invention has the following characteristics: (1) Most of the additive strategies that have been developed so far are aimed at solving the stability problem of perovskite solar cells under specific aging conditions. There are few studies on improving the service life of perovskite solar cells under the day-night cycle working mode.

[0091] (2) Most of the additive strategies currently developed have a specific role, such as defect passivation, crystallization regulation or lattice anchoring. In combination with the above embodiments, the chalcogenide ligand material developed in the present invention has a dual role: first, Ph-Se-Cl reacts with FAI during thermal annealing to form volatile substances, which optimizes the crystal growth dynamics of perovskite and obtains a room temperature stable pseudo-cubic phase FAPbI3 with higher symmetry; in addition, the ligand material reacts with PbI2 to form lead salts and anchors at the grain boundaries, further inhibiting the light- and heat-induced lattice expansion and contraction and eliminating lattice stress changes. This dual strategy stabilizes the perovskite lattice from the root and comprehensively improves the stability of perovskite solar cells.

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A perovskite solar cell based on a chalcogenide ligand material, characterized in that: The invention comprises a perovskite thin film layer doped with a chalcogenide ligand material.

2. The perovskite solar cell based on chalcogenide ligand material according to claim 1, characterized in that: The chemical structural formula of the chalcogenide ligand material is as follows: ; Wherein, A is a chalcogen element; X is a halogen or a pseudohalogen.

3. The method for preparing a perovskite solar cell based on a chalcogenide ligand material according to claim 1, comprising the following steps: An electron transport layer is prepared on a conductive substrate; a perovskite precursor solution doped with a chalcogenide ligand material is then spin-coated on the electron transport layer, followed by heat treatment to obtain a perovskite film layer; a hole transport layer and an anode are then sequentially prepared on the perovskite film to obtain a perovskite solar cell based on a chalcogenide ligand material.

4. A perovskite film based on a chalcogenide ligand material, characterized in that: The chemical structural formula of the sulfide ligand material is shown in claim 2.

5. The method for preparing a perovskite film based on a chalcogenide ligand material according to claim 4, comprising the following steps: heat treating a perovskite precursor solution doped with a chalcogenide ligand material to form a film, thereby obtaining a perovskite film based on a chalcogenide ligand material.

6. The preparation method according to claim 3 or 5, characterized in that: The heat treatment is performed at 140-160°C for 15-30 minutes; the doping concentration of the perovskite solution doped with the chalcogenide ligand material is 0.2-2.0 mg mL -1 .

7. A day-night cycle stability test method for perovskite solar cells, comprising the following steps: testing the power of the perovskite solar cell under sunlight and then avoiding light; repeating the above test process to complete the day-night cycle stability test of the perovskite solar cell.

8. Use of the perovskite solar cell based on chalcogenide ligand material according to claim 1 in the preparation of solar energy devices.

9. Use of the perovskite film based on the chalcogenide ligand material according to claim 4 in the preparation of perovskite solar cells.

10. Use of the chalcogenide ligand material according to claim 2 in preparing a perovskite solar cell or a perovskite film for a perovskite solar cell.

Citation Information

Patent Citations

  • Photovoltaic device comprising a metal halide perovskite and a passivating agent

    CN106062983A

  • Perovskite solar cell capable of inhibiting photolysis of passivation layer and preparation method

    CN111640871A

  • Flexible perovskite solar cell based on small organic molecules capable of in-situ crosslinking

    CN115942852A

  • Perovskite solar cell passivated by sulfur-containing passivator

    CN116322094A

  • Trans-perovskite solar cell for repairing thermally induced damage of perovskite based on self-healing characteristic material and preparation method of trans-perovskite solar cell

    CN118591247A